Development of an Online Training Program for Public Library Staff to Deliver Autism Friendly Story Time Sessions. Issue 4 (1st October 2020) - Paynter, Jessica; Simpson, Kate; O'Leary, Kate; Hurley, Andrea; Wicks, Rachelle; Westerveld, Marleen
ABSTRACT: Children on the autism spectrum are at risk of persistent impairments in literacy. Early literacy opportunities (e.g., Library Story Times) are thus important, but children on the spectrum experience barriers to participating in these. Our objective was to develop an online training package to support implementation of autism-friendly Story Time sessions for librarians. A mixed-methods approach was undertaken across three phases. Phase 1 included face-to-face training development and implementation ( n = 22) and quantitative evaluation (autism knowledge, confidence, and social validation). Phase 2 included implementation in libraries and qualitative evaluation of the utility and implementation of training through librarian interviews ( n = 5). Phase 3 included translation and implementation of an online module ( n = 22) and quantitative evaluation (autism knowledge, confidence, and social validity). Participation in both training modalities increased knowledge of autism and confidence to include children on the spectrum in Story Time sessions. Social validity of both modalities was rated highly. Librarians indicated changes in practice following training, although full implementation of the package was limited to librarians receiving additional coaching. Limitations, future research, and implications in terms of future training and supports including the value of ongoing coaching for implementation are discussed.